2016
DOI: 10.1093/cz/zow034
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction and survival in the city: which fitness components drive urban colonization in a reed-nesting waterbird?

Abstract: Processes of adaptation to urban environments are well described for relatively few avian taxa, mainly passerines, but selective forces responsible for urban colonization in ecologically different groups of birds remain mostly unrecognized. The aim of this article is to identify drivers of recent urban colonization (Łódź, central Poland) by a reed-nesting waterbird, the Eurasian coot Fulica atra. Urban colonizers were found to adopt a distinct reproductive strategy by maximizing the number of offspring (carryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…During the city‐wide bird surveys of Łódź made from 1994 to 2002 breeding attempts of coots were recorded at 19 sites located in the outer zones of the city with low or moderate urbanization level (Janiszewski et al ). The surveys were repeated in 2009–2014 and showed that coots have colonized 13 waterbodies located mostly in the city centre (Minias ). All three cities (Łódź, Poznań, and Warszawa) belong to the five most populated urban sites in Poland (540 000–1 740 000 inhabitants; 262–517 km 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…During the city‐wide bird surveys of Łódź made from 1994 to 2002 breeding attempts of coots were recorded at 19 sites located in the outer zones of the city with low or moderate urbanization level (Janiszewski et al ). The surveys were repeated in 2009–2014 and showed that coots have colonized 13 waterbodies located mostly in the city centre (Minias ). All three cities (Łódź, Poznań, and Warszawa) belong to the five most populated urban sites in Poland (540 000–1 740 000 inhabitants; 262–517 km 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Eurasian coots nest in emergent shore vegetation on a wide range of still or slow‐flowing waters (Snow & Perrins ), but are usually secretive and highly timid towards humans while nesting in natural habitats. Although the recent urban colonization in central Poland yielded large reproductive benefits for this species (Minias ), it may be expected that those fitness advantages could have been only attained via a number of behavioural adaptations. To test this hypothesis, changes in three components of coot behaviour, that is nest‐site selection, nest attendance patterns and nest defence behaviour, were evaluated along the urbanization gradient of Łódź, a large city in central Poland.…”
Section: Introductionmentioning
confidence: 99%
“…Taking these results into account, it seems that food availability may not be an important component of territory selection by coots nesting in an urban landscape, or at least it may be of second importance when compared to brood safety that is provided by emergent vegetation. Previous comparisons of urban and suburban coot populations revealed that urban‐dwelling individuals were in much better nutritional condition than suburban conspecifics, which was mainly attributed to the availability of anthropogenic food (Minias, ). However, it is possible that an access to natural food resources (submerged macrophytes and aquatic invertebrates; Brinkhof, ) combined with food provided deliberately by humans makes urban coots virtually unlimited in terms of food availability.…”
Section: Discussionmentioning
confidence: 99%